Pengaruh Endorser Instagram Terhadap Keputusan Pembelian Produk Fashion: (Studi Kasus Pada Gen Z USU) - Marbun, Yuana Widya Angeline; Raissa Aurellia; Tampubolon, Claudia Yonica Br; Saragih, Mernita Sari; Aritonang, Robbi Pradita; Siregar, Afrila Mulyati; Siregar, Onan Marakali (Cantaka: Jurnal Ilmu Ekonomi dan Manajemen, 2024)
The current digital era continues to develop, the role of Instagram endorsers in influencing purchasing decisions for fashion products, especially among Gen Z. Endorsers are considered brand representations that play a key role in branding and marketing communication strategies. The goal of celebrity endorsement, as a marketing tactic, is to use one or more celebrities to advocate for a specific good or service. The purpose of this study is to gain a thorough understanding of the ways in which Gen Z consumers on USU campuses are influenced by Instagram influencers when making fashion-related purchases. This study employed a quantitative research design with a sample size of seventy USU students interested in fashion and who use Instagram to follow celebrity endorsers. This study used simple linear regression analysis as its data analysis method. The findings demonstrated that Instagram endorsers had an impact on purchase decisions, as seen by the t value of 7.833>1.667, which was reached above the t table. Keywords: Endorse, Instagram, Purchase Decision, Brand Image, USU